I-CART: an innovative way engaging with the community / Nor Faridah Ahmad Roslan ... [et al.] - Ahmad Roslan, Nor Faridah; Mohd Ali Piah, Hanizah; Jamil, Nur Farah Farhana; Sauti, Munirah; Razali, Norsyefa; Aziz, Abdul Qahhar Muzakkar (2020)
The need for caregiving is growing, with the increasing numbers of elderly and people with disabilities. In Malaysia, caregiver support is limited and expensive. Transferring the knowledge and skill of carer training requires time, cost and motivation. The carer training provided in the hospital usually inadequate because limited time, resources and lack of family preparedness to learn. Therefore, Interdisciplinary Caregiver Rehabilitation Training (I-CART) module is innovated to engage with the caregivers in community and upgrade their knowledge related to caregiving of bedridden people, in effective way. ICART provides 5 modules, which is a core knowledge and skill that the caregiver must know to handle a bedridden patient. The modules are provided by doctors, psychologist, rehabilitation nurse, physiotherapist, occupational therapist and speech therapist. Methods of module delivery are by didactic teaching, real-life demonstration, sharing session and practical session. This is the two days module provided in a small targeted group and a platform of health professionals to engage with community differently. It is cost-effective, unique and has commercialization value targeting the informal caregiver and private institutions that providing caregiver services. Therefore, the health burden related to bedridden patient and caregiver will be minimized, reduce healthcare cost and better quality of life.